The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10072-021-05411-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract dysfunction in Parkinsonian syndromes

Abstract: Purpose of review:The aim of this review is to outline the clinical presentation, pathophysiology and evaluation of lower urinary tract (LUT) dysfunction in Parkinson's disease and other parkinsonian syndromes including multiple system atrophy, dementia with Lewy bodies, progressive supranuclear palsy and corticobasal degeneration.Recent findings: LUT dysfunction commonly occurs in neurological disorders, including patients with parkinsonian syndromes. The pattern of LUT dysfunction and its severity are variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Lesions in the spinal cord may cause DESD and incomplete bladder emptying. Sacral or infrasacral lesions result in denervation of bladder and/or sphincters with incompetent sphincter and poorly sustained/absent detrusor contractions (Vichayanrat et al, 2021). As aforementioned, DO may be correlated with the emergence of a capsaicin-sensitive C-fiber-mediated spinal micturition reflex caused by a reorganization of synaptic connections in the spinal cord (Banakhar et al, 2012).…”
Section: Spinal Cord Injurymentioning
confidence: 98%
“…Lesions in the spinal cord may cause DESD and incomplete bladder emptying. Sacral or infrasacral lesions result in denervation of bladder and/or sphincters with incompetent sphincter and poorly sustained/absent detrusor contractions (Vichayanrat et al, 2021). As aforementioned, DO may be correlated with the emergence of a capsaicin-sensitive C-fiber-mediated spinal micturition reflex caused by a reorganization of synaptic connections in the spinal cord (Banakhar et al, 2012).…”
Section: Spinal Cord Injurymentioning
confidence: 98%
“…Often, storage symptoms (frequency/urgency±urge incontinence) precede voiding symptoms (reduced stream/flow, dribbling) 46 47…”
Section: Diagnosing Msamentioning
confidence: 99%
“…Similar to the observations in PD, constipation is a common autonomic disorder in MSA [ 11 ]. However, it has been reported that PD and MSA have different preganglionic and postganglionic fiber dysfunction in the autonomic nervous system and that dysuria in both diseases also has different symptoms even at an early stage [ 12 , 13 ]. Therefore, the differences in the symptoms of constipation may also help in the early diagnosis of these seemingly similar neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%